Development and validation of the novel subclassification of pN3 for patients with esophageal cancer - Ma, Keru; Wang, Hao; Fang, Chengyuan; Jiang, Xiangyu; Ma, Jianqun (Frontiers in Oncology, 2023)
Background: Patients with stage pN3 esophageal cancer (EC) have a large number of metastatic lymph nodes (mLNs) and have poor prognosis. This study was to elucidate whether subclassification of pN3 according to the number of mLNs could improve the discrimination ability of EC patients. Methods: This study retrospectively analyzed patients with pN3 EC from the Surveillance, Epidemiology, and End Results (SEER) database as a training cohort and SEER validation cohort. Patients with pN3 esophageal cancer from the Affiliated Cancer Hospital of Harbin Medical University were used as the validation cohort. The optimal cutoff value of mLNs was identified using the X-tile software, and group pN3 into pN3-Ⅰ and pN3-Ⅱ based on mLNs. Kaplan-Meier method and log-rank test were used to analyze the disease-specific survival (DSS). The Cox proportional hazards regression analysis was used to identify the independent prognostic factors. Results: For the training cohort, patients with 7 to 9 mLNs were categorized as pN3-Ⅰ, while those with more than 9 mLNs were categorized as pN3-Ⅱ. There were 183 (53.8%) pN3-Ⅰ and 157 (46.2%) pN3-Ⅱ. The 5-year DSS rates of pN3-I and pN3-II in the training cohort were 11.7% and 5.2% (P=0.033), and the pN3 subclassification was an independent risk factor associated with patient prognosis. More RLNs may not improve patient prognosis, but the use of mLNs/RLNs is effective in predicting patient prognosis. Furthermore, the pN3 subclassification was well validated in the validation cohort. Conclusion: Subclassification of pN3 can better distinguish survival differences in EC patients.